THE EFFECT OF EXCLUSIVE BREASTFEEDING ON THE TREATMENT OF JAUNDICE INFANTS: A LITERATURE REVIEW - Ilham, Andi Yulianti; Tosepu, Ramadhan ((Jurnal Ilmiah Mahasiswa Kesehatan Masyarakat), 2024)
Jaundice or hyperbilirubinemia is a normal condition in newborn babies during the first week due to incomplete liver function in the process of removing bilirubin from the baby's bloodstream. Hyperbilirubinemia occurs when the blood's bilirubin level exceeds 13mg/dL. Based on 2007 basic health research (Riskesdas) data regarding the causes of neonatal death, hematological disorders/hyperbilirubinemia is the 5th cause of neonatal morbidity with a prevalence of 5.6% after respiratory disorders, prematurity, sepsis, and hypothermia. , There is no multicenter data in Indonesia regarding hyperbilirubinemia. The latest data on the prevalence of severe hyperbilirubinemia (>20mg/dL) is 7%, with acute encephalopathic hyperbilirubinemia at 2%. This multicenter data is not representative of data from all of Indonesia because it only comes from eight hospitals in big cities (Jakarta, 6 hospitals; Kupang, one hospital, and Manado, one hospital). The method used in writing this article is a literature review. This study uses the search engines Google Scholar, Pubmed, Science Direct, Emerald, and Biomed with an article period between 2018-2022, both nationally and internationally, relevant to the topic. Based on an article review conducted on 7 appropriate articles, it was found that there was an influence of breastfeeding on the care of jaundiced babies. Based on the research results, it can be concluded that breastfeeding can prevent neonatal jaundice. Keywords: exclusive breastfeeding, baby jaundice, neonatal jaundice.